Emerging Threats to Energy Security and Stability - McPherson, Hugo.; Duncan Wood, W.; Robinson, Derek M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
With the global economy set to be largely dependent on oil and gas for the next twenty to thirty years, and global terrorism more prevalent and more focused on economic targets, the threat to energy sources and supply is real and increasing. "Emerging Threats to Energy Security and Stability" is a compendium of papers from the 2004 NATO Workshop at Windsor Castle organized by the Windsor Energy Group and MEC International. The workshop was co-directed by Sir David Gore Booth, former UK Ambassador to Saudi Arabia and Middle East Director - Foreign and Commonwealth Office, and Dr. Evgeny Velikhov, President, the Russian Research Center, Kurchatov Institute. Representatives from 20 countries participated in the workshop; including experts and policy makers from key governments, international organizations and the private sector. The papers examine strengths and vulnerabilities of global energy infrastructure, assessing emerging threats to energy security, and developing recommendations for energy security strategies to counter the threats posed by supply imbalance, regional instability and terrorism. Aimed at those involved in infrastructure security as well as the Energy Sector, the publication also includes background papers on the World Energy Market, covering such issues as the Geo-Political Future of the Gulf, China and OPEC, and regional briefings on Egypt, Saudi Arabia, Central Asia and the Caspian Basin.
Executive Summary -- A Summary of the Discussions -- Prospects for the Global Energy Market -- An Overview -- A Political Perspective -- An Analytical Perspective -- An Economic Perspective -- National Strategic Energy Interests -- Energy Security and Unresolved Conflict in the Caucasus -- Prospects for Russian Energy -- Evolving Roles of Multilateral Organisations and the Private Sector -- Overview -- The International Energy Forum and Energy Security & Stability -- The View from Brussels -- Regional Challenges: the Middle East -- National Strategic Energy Interests and Creating Regional Stability in the Middle East -- Emerging Threats to Energy Security and Stability -- IRAQ: A Japanese Perspective -- Regional Challenges - North Africa -- Libya -- The North African Challenge -- Regional Challenges - the Caucasus Region - Caspian & Black Sea Basins -- Turkey & Nato -- Prospects for the Caucasus, the Corridor between Two Continents - Keynote Address -- Tatarstan: Euro Islam in the Volga Region -- Critical Energy System Infrastructure (CESI) - Emerging Threats to Shipping and Pipelines -- Shipping: Vital, Vulnerable and Little Understood -- The Straits of Malacca: Critical Sea-Lane Chokepoint -- Background Papers on the World Energy Market -- The Geo-Political Future of the Gulf -- China and Opec -- Egypt - a Promise Yet to be Fulfilled -- Egypt's Race for Gas Export Markets -- Saudi Arabia -- Saudi Society -- Central Asia and the Caspian Basin -- Initiatives Emanating from the Workshop -- Initiative: Energy Security and Unresolved Conflict in the Caucasus -- Initiative on Pipelines Ports and Shipping Security - Building Public-Private Cooperation -- Energy Security & Nato Strategic Interests After 9/11 -- Press Coverage -- Epolitix -- Epolitix -- Bloomberg News -- The Times.
Keywords: ECONOMICS; GEOGRAPHY; ENGINEERING ECONOMY; ECONOMIC POLICY; EUROPE -- ECONOMIC POLICY; INTERNATIONAL ECONOMICS; SOCIAL SCIENCES; ECONOMICS/MANAGEMENT SCIENCE; ECONOMIC POLICY; EUROPEAN INTEGRATION; INTERNATIONAL ECONOMICS; ECONOMIC GEOGRAPHY; SOCIAL SCIENCES, GENERAL; ENERGY ECONOMICS